The association of education and household income with the lifetime risk of incident atrial fibrillation: The Framingham Heart study - Feven Ataklte; Quixi Huang; Jelena Kornej; Favel Mondesir; Emelia J Benjamin; Ludovic Trinquart (American Journal of Preventive Cardiology, 2022)
Background: Social determinants of health, in particular education and income, influence the incidence, management, and outcomes of cardiovascular diseases including atrial fibrillation (AF). Data are limited on the associations of socioeconomic status with lifetime risk of incident AF. Methods: We selected 2172 FHS participants (51% women) who were free of AF at the index age of 55 years. We assessed educational attainment (≥college) at the last exam prior to index age and household income ($40k/50k/≥55k depending on the FHS cohort). We estimated the lifetime risk of AF as the cumulative incidence of AF, accounting for the competing risk of death, at age 95 years. We analyzed strata defined by education and household income separately, and by combining education and household income. We adjusted analyses for sex, height, weight, systolic and diastolic blood pressure, current smoking, alcohol consumption, use of antihypertensive medication, diabetes, history of myocardial infarction, and history of heart failure. Results: Over a mean follow-up of 13 years, 265 participants developed incident AF. The lifetime risk of developing AF was 32.5% (95%CI, 26.5% to 38.5%) and 32.5% (95%CI, 28.7% to 38.3%) among participants with lower and higher education attainment (p=0.98). The lifetime risk of developing AF was 32.1% (95%CI, 26.7% to 37.5%) and 31.8% (95%CI, 26.6% to 36.9%) among participants with lower and higher household income (p=0.79). There was no evidence of interaction between education and income on lifetime risk of AF (p = 0.84). Results were similar in subgroups of women and men. Conclusion: In our community-based sample, there was no evidence of an association between education or household income and lifetime risk of AF.